EVALUATION OF DUAL BANKING SYSTEM IN BANKING IN INDONESIA - Amanatun Nisfah Nurun Nikmah; Tulus Suryanto; Surono Surono (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2020)
Evaluation of Dual Banking System in Indonesia. Dual Banking System is the application of two banking systems in one banking institution, namely conventional banking and Islamic banking. Indonesia can optimize the dual banking system through strength share and weakness cover, namely Islamic banks are generally superior in terms of a more stable system in the face of market changes but have deficiencies in infrastructure, whereas conventional banks have large market and capital access and more infrastructure complete, but very vulnerable to crises due to the negative factors of economic integration which are already very strong. The superiority of the dual banking system concept is seen in two separate systems that operationally do not affect each other, but have one common goal, namely financial stability that supports economic growth. So, to achieve this goal the two systems can work together in external factors such as access to capital, infrastructure, supervision or clearing systems that can help interbank liquidity.